Advancing Educational Practices: Implementation of the Index Card Match Method in Islamic Learning - Zulvia Trinova; Ilman Nasution; Fauza Masyhudi; Nurjannah Nurjannah; Mayang Belia Sameto; Fitriani Fitriani (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
The purpose of this research is to determine the application of the Index Card Match method in Islamic learning in high schools, to find out the learning outcomes of students using the Index Card Match method in high school jurisprudence learning. This research was a quasi-experimental design with a Randomized Control Group Only Design, the research subjects used were students at Senior High School as the experimental class and High School students as the control class. The instrument for the affective domain is an observation sheet and for the cognitive domain is an objective question. Final data analysis in this study used the normality test, homogeneity test and t-test. Based on the research results, the average student learning outcomes for the cognitive domain of the experimental class were 76.4 and for the control class 69.05. Meanwhile, for the affective domain, the average student attitude/value results for the experimental class were 80.7875 and for the control class 67.9275. Data obtained tcount >ttable, until H0 rejected and H1 accepted. Thus, the learning outcomes of students using the Index Card Match method are higher than the learning outcomes using conventional learning in high schools